Quantum forgery attacks on COPA, AES-COPA and marble authenticated encryption algorithms - Xu, Yinsong; Liu, Wenjie; Yu, Wenbin (Quantum information processing, 2021)
The classic forgery attacks on COPA, AES-COPA and Marble authenticated encryption algorithms need to query about 2 n / 2 times, and their success probability is not high. To solve this problem, the corresponding quantum forgery attacks on COPA, AES-COPA and Marble authenticated encryption algorithms are presented. In the quantum forgery attacks on COPA and AES-COPA, we use Simon’s algorithm to find the period of the tag generation function in COPA and AES-COPA by querying in superposition, and then generate a forged tag for a new message. In the quantum forgery attack on Marble, Simon’s algorithm is used to recover the secret parameter L , and the forged tag can be computed with L . Compared with classic forgery attacks on COPA, AES-COPA and Marble, our attack can reduce the number of queries from O ( 2 n / 2 ) to O ( n ) and improve success probability close to 100%.